Tax treatment of foreign direct investments under the Investment Promotion Law 16-09 - Remmache, Soumia; Rikli, Saddik (Journal of Human Sciences, 2021)
The Investment Promotion Law No. 16-09 came with many tax incentives in order to encourage foreign direct investment outside the hydrocarbons sector, through which the legislator tried to work to improve the tax treatment, by reshaping the tax benefits to four levels. In implementation of this law, several regulatory texts were issued aimed at Simplifying the procedures for taking advantage of these advantages by canceling the permit system, requesting benefits, and compensating it with the registration system that is carried out by the National Agency for Investment Development. Despite the tax incentives provided, the volume of the influx did not rise to the level of opportunities and capabilities available, which confirms that there are a number of obstacles that hinder the success of the tax incentive policy. Its effectiveness and success is linked to the availability of several factors, including tax in nature and some of the non-tax nature related to the investment climate.